Social and legal aspects of drug abuse in Malaysia / Zainal Adzam Abdul Ghani - Zainal Adzam , Abdul Ghani (1976)
The object of this paper is to study the problem of drug abuse in this country, a social problem of a serious nature and magnitude. To appreciate the problem, we need only take a cursory glance at our daily newspapers which will reveal, to us that the problem of drug abuse in this country is very much alive and serious. Almost every day, one could re ad about the detection, arrest prosecution and conviction of drug offenders. At the same time, constant warnings and reminders of the dangers of drug abuse are issued and harped upon through the mass media. Despite all this, there seems to be no lessening of the problem in sight, but instead there is an apparent increase in the proportion of the problem. Available statistics prove beyond doubt that there has been a steady increase in the. amount of drugs available in this country per year during the last six years. The amount of opium, morphine, heroin, ganja and psychotropic pills seized by law enforcement agencies during that period is very considerable as can be seen from the statistics below.